2012
DOI: 10.1002/qua.23302
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical study on plasmon resonances in small ring clusters

Abstract: The collectivity of the electronic motion in small sodium clusters with ring structure is studied by time-dependent density functional theory. The formation and development of collective resonances in the absorption spectra were obtained as a function of the ring radius. In small ring clusters, besides the lower-energy mode and the higher-energy mode, there is another plasmon resonance mode, that is, the reverse two-dipole mode. For the reverse two-dipole mode, the formations of these two dipoles are due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…who showed that collective excitations exist even for very small clusters. More recent work addresses the mechanism of the collective excitations and field enhancement in higher dimension clusters using TD-DFT. For example, Ma et al . studied the sensitivity of plasmon resonance in Au nanoparticles and their dimers as a function of the particle size and the interparticle distance .…”
mentioning
confidence: 99%
“…who showed that collective excitations exist even for very small clusters. More recent work addresses the mechanism of the collective excitations and field enhancement in higher dimension clusters using TD-DFT. For example, Ma et al . studied the sensitivity of plasmon resonance in Au nanoparticles and their dimers as a function of the particle size and the interparticle distance .…”
mentioning
confidence: 99%